Estratégia de operações no varejo: um estudo sobre perfilar mercado, produto e operações no setor de supermercados - Lima, Juaceli Araújo de (2006)
The objective of this Thesis is to investigate the strategic alignment between market end operations in the retail supermarket sector applying the concept product profiling by Hill (1993). To the developing was utilized a methodology of the cases study had were a evolvement if the action research into on of the RedeMais supermarkets. Through the interview, discussion and direct action became possible collect information necessary to direction this work, absorbing and understanding the methodology and thought form, action and management. This work contribute to development the create of the model adapted of the manufactory to service, the product matrix of the Hill, in which serve a tool to uncover the origins of misalignment that occur over time and to illustrate the phenomenon to executives gone support to decision